What is the value of 6 (x – 2) (x – 3) + 4(x – 2) (x – 5) when x = -3?

Question

What is the value of 6 (x – 2) (x – 3) + 4(x – 2) (x – 5) when x = -3?

in progress 0
Thành Đạt 1 year 2021-08-31T14:33:48+00:00 1 Answers 7 views 0

Answers ( )

    0
    2021-08-31T14:35:46+00:00
    • Answer:

    340

    • Step-by-step explanation:

    Hi there !

    6(x – 2)(x – 3) + 4(x – 2)(x – 5) =

    replace x

    = 6(-3 – 2)(- 3 – 3) + 4(-3 – 2)(-3 – 5)

    = 6(-5)(-6) + 4(-5)(-8)

    = 6(30) + 4(40)

    = 180 + 160

    = 340

    Good luck !

Browse

Giải phương trình 1 ẩn: x + 2 - 2(x + 1) = -x . Hỏi x = ? ( )